Tyrphostin AG1478 inhibits encephalomyocarditis virus and hepatitis C virus by targeting phosphatidylinositol 4-Kinase IIIα - Dorobantu, Cristina M.; Harak, Christian; Klein, Rahel; Linden, Lonneke van der; Strating, Jeroen R. P. M.; Schaar, Hilde M. van der; Lohmann, Volker; Kuppeveld, Frank J. M. van (Antimicrobial agents and chemotherapy, 2016)
Encephalomyocarditis virus (EMCV), like hepatitis C virus (HCV), requires phosphatidylinositol 4-kinase IIIα (PI4KA) for genome replication. Here, we demonstrate that tyrphostin AG1478, a known epidermal growth factor receptor (EGFR) inhibitor, also inhibits PI4KA activity, both in vitro and in cells. AG1478 impaired replication of EMCV and HCV but not that of an EMCV mutant previously shown to escape PI4KA inhibition. This work uncovers novel cellular and antiviral properties of AG1478, a compound previously regarded only as a cancer chemotherapy agent.